Tiktok Sebagai Ruang Budaya Baru dalam Kajian Antropologi Digital rerhadap Pembentukan Identitas Dan Interaksi Sosial Generasi Muda - St. Junaeda (SOCIETIES: Journal of Social Sciences and Humanities, 2026)
Abstract. The rapid growth of digital technology has transformed the ways individuals communicate, construct identities, and engage in social interactions. Among various social media platforms, TikTok has emerged as a prominent cultural space where young people actively create, share, and consume content. Beyond its function as an entertainment platform, TikTok serves as a dynamic environment in which cultural meanings, values, symbols, and social practices are continuously produced and negotiated. This study aims to examine TikTok as a new cultural space and to explore its role in shaping identity formation and social interactions among young people from the perspective of digital anthropology. This research employs a qualitative approach using digital ethnography. Data were collected through non-participant observation of TikTok accounts, videos, captions, hashtags, and user interactions within the platform. The study focuses on how young users represent themselves, construct digital identities, and engage in social relationships through content creation and participation in online communities. The collected data were analyzed thematically to identify recurring patterns related to self-representation, cultural expression, and social engagement in the digital environment. The findings indicate that TikTok functions as an important cultural arena where young people negotiate identities, express creativity, and establish social connections beyond geographical boundaries. Through the use of visual narratives, trends, and interactive features, users actively participate in the production and reproduction of digital culture. At the same time, the platform facilitates the emergence of virtual communities and new forms of social interaction shaped by algorithms and participatory culture. This study highlights the significance of digital anthropology in understanding the cultural transformations brought about by social media and demonstrates how TikTok has become an influential space for identity construction and social interaction among contemporary youth. Keywords: Antropologi Digital, TikTok, Identitas Digital, Interaksi Sosial, Media Sosial, Budaya Digital, Budaya Generasi Muda, Ruang Budaya Digital